Fluid resuscitation in adults with severe infection and sepsis: a systematic review and network meta-analysis - Song, Binglin; Fu, Kangrui; Zheng, Xiangde; Liu, Chun (Frontiers in Medicine, 2025)
IntroductionThe choice of optimal resuscitation fluid for patients with septic shock remains a controversial topic. The 2021 Sepsis Surviving Campaign Guidelines strongly recommend using crystalloids as the first-line resuscitation fluid for adults with sepsis or septic shock, with balanced crystalloids as a weak recommendation. However, two large-scale network meta-analyses in 2020 concluded that balanced crystalloids are most advantageous. This study reevaluates the efficacy and safety of different resuscitation fluids in septic shock through a network meta-analysis (NMA).MethodsDatabases including PubMed, EMBASE, and WOS were searched, and reference lists of relevant literature up to September 2024 were reviewed. Studies involving adult patients with sepsis requiring fluid resuscitation were selected. The fluids covered include balanced crystalloid (BC), saline, iso-oncotic albumin (Iso-Alb), hyper-oncotic albumin (Hyper-Alb), low molecular weight hydroxyethyl starch (L-HES), high molecular weight hydroxyethyl starch (HES), and gelatin. A network meta-analysis was conducted to assess the effects of different fluid types.ResultsA total of 32 RCTs were included in the analysis. The NMA probability ranking results show that balanced crystalloid (BC) had the lowest all-cause mortality rate, with the highest SUCRA value (83.1%). Gelatin was shown to confer the greatest advantage in terms of kidney injury, with the highest SUCRA value (80.7%). Hyper-oncotic albumin had the lowest occurrence of renal replacement therapy events, showing the highest SUCRA value (94.1%). Patients treated with balanced crystalloids had the shortest ICU stays and hospital lengths of stay.ConclusionBalanced solutions (BS) are the preferred resuscitation fluids for septic shock. High molecular weight hydroxyethyl starch (H-HES) is associated with increased risks of mortality, acute kidney injury (AKI), and renal replacement therapy (RRT), as well as prolonged hospital stays, and its use is advised against. Gelatin is associated with poorer outcomes in terms of mortality, continuous renal replacement therapy (CRRT), and length of hospital stay.Systematic review registrationRegistration ID: INPLASY2024100049 https://doi.org/10.37766/inplasy2024.10.0049.